Drainage reorganization and alluvial architecture of endorheic basins: The Lower Cretaceous record of the Chubut Group in the Golfo San Jorge Basin (Patagonia, Argentina) - Paredes, José (2024)
Fil: Paredes, José. Geology Department, FCNyCS, Universidad Nacional de la Patagonia “San Juan Bosco”. Argentina.